PERAN PEREMPUAN DALAM MEMBANTU PEREKONOMIAN KELUARGA DI DESA TEWAH KABUPATEN GUNUNG MAS - Rahmad Rafi’i; Syamsuri Syamsuri (Prodi Sosiologi FISIP UPR, 2021)
The role of the female farmers in the household at this time has shifted to the realm outside house, in the sense that the women go out of the houses to work to help husbands. The phenomenon of the role of the women is very large, it can be seen from the enthusiasm of the women to work. These female farmers in Tewah village works twice a day, in the morning and in the evening. This situation makes women have two roles, namely the role of working to take care of the household and the role of working to help the family economy. This paper aimed to describe and analyze the role of the women in helping family economy in Tewah village, Tewah sub-district, Gunung Mas district. This research used descriptive qualitative method. The data was collected through observation and interview. Moreover, the data w as analyzed by using interactive analysis technique. The results of this research showed that the role of the women was very helpful in improving the family economy because the income of the head of the family was still not fully able to meet the needs of the family. The women or the housewives in Tewah village worked as the vegetable farmers, the broom craftswomen, the dried fish sellers, the tailors, the online sellers, and opened basic food stalls to help the family economy. The sociological side in this research was the role and the working spirit of the women in helping the family economy as a form of serving the family and the role of women which results in social interaction to the family or the society because the role of women in the family cannot be separated from the surrounding society in order to create the harmonious society.